"His lack of a mask ruined everything." Restaurant customer satisfaction during the COVID-19 outbreak: An analysis of Yelp review texts and star-ratings. (September 2021) - Kostromitina, Maria; Keller, Daniel; Cavusoglu, Muhittin; Beloin, Kyle
Abstract: The aim of the study was to provide practical advice to restaurant managers for improving star ratings as well as information for researchers on how the pandemic has impacted established determinants of satisfaction. The study examined criteria used by restaurant customers in assigning star-ratings on Yelp during the COVID-19 pandemic using keyword analysis and Multiple Correspondence Analysis. In evaluating restaurants, the reviewers focused on service, overall experience, and food quality. Service was discussed in relation to the pandemic and included safety of the dine-in experience, contrasted with take-out options and compliance with COVID-19 guidelines. These criteria applied differently with lower-star reviews focusing on safety, social distancing, and mask policies. Higher-star reviews focused on take-out/delivery services, high-quality food, and an overall positive experience. The study provides valuable contributions to our understanding of how the COVID-19 pandemic will impact the restaurant sector in a post-pandemic world. Highlights: Keywords MCA in COVID-19-related restaurant reviews on Yelp was done to define star ratings Low star reviews focused on safety of dine-in and compliance with COVID-19 guidelines High star reviews are characterized by availability of take-out/delivery